Application possibility of ophthalmic heparin ointment as an artificial tear (preliminary report) - V.D. Yartsev (РМЖ "Клиническая офтальмология")
V.D. Yartsev Scientific Research Institute of Eye Diseases, Moscow, Russian Federation Abstract Currently, there is an increase in the incidence of dry eye syndrome (DES) associated with tear production deficiency and an increase in tear fluid evaporation, and mixed conditions are recorded in 80% of cases. This is the reason why evaluation of clinical effectiveness of the drugs used for the treatment of mixed forms of DES is high priority. Aim: to estimate change of tear fluid amount in patients with dry eye diseases after administration of heparin ointment. Patients and Methods: clinical research included 11 patients (21 eyes) with a previously diagnosed DES and with complains on ocular discomfort, sandy-gritty sensation, eyelid itching. All patients underwent a lacrimal meniscometry based on optical coherence tomography with determination of the depth and height of the tear meniscus. In all cases, heparin ocular ointment was prescribed once a day in the evening (PARIN-POS®, URSAPHARM Arzneimittel, GmbH). Lacrimal meniscometry was performed again in 5 days. The difference of morphometric values was estimated with non-parametric Wilcoxon test. Results: we found that the difference of the values of depth and height before and after the treatment was statistically significant (p=0.05 and 0.03). Median of height change was 24 mkm (maximum — 216 mkm), median of depth change was 38 mkm (maximum — 425 mkm). Conclusion: conducted research showed that during the first week after prescription of heparin-containing ocular ointment PARIN-POS® in patients with dry eye diseases a statistically significant growth of tear meniscus depth and height occurs. This is associated with noted decrease of ocular discomfort. Detected changes are the base of the conclusion that tested drug has potential clinical effects that should be analyzed in other clinical trials. Key words: dry eye diseases, artificial tear, ocular ointment, heparin, PARIN-POS. For citation: Yartsev V.D. Application possibility of ophthalmic heparin ointment as an artificial tear (preliminary report).  RMJ “Clinical ophthalmology”. 2018;3:129–133.